GAMBARAN PENILAIAN GURU TENTANG PELAKSANAAN PROGRAM USAHA KESEHATAN SEKOLAH (UKS) DI SEKOLAH DASAR NEGERI No. 060910 MEDAN TAHUN 2017 - Connie Melva Sianipar (Elisabeth Health Jurnal, 2017)
School health program is an effort to nurture and develop healthy habits conducted in an integrated manner through educational programs, health services and health care in the school environment. Goals: The purpose of this study is to identify the implementation of teacher’s evaluation about School Health Unit (UKS) program in the State Primary School No.060910 Medan 2017. Methods: The research is a descriptive study with a sample of 23 people is a teacher of elementary school No. 060 910 Medan 2017. Field data collection tool used was a questionnaire. Results: The results of this study obtained the overall implementation of the UKS program implemented fairly that is 56.5%. UKS implementation of school health education activities are carried out fairly, that is 62.5%, the activities carried out with sufficient health care, which is 65.2% and the activities of health coaching healthy school environment performing well, which is 73.9%. Conclusion: Puskesmas are expected to improve their cooperation and performance with schools in their work areas, especially in improving health services. Puskesmas with schools need to discuss the UKS activities plan that will be done in school, so that can be arranged schedule of implementation and their respective duties. Puskesmas are also expected to work together both in materials and ideas to improve the implementation of UKS in each school.